31. Telemedicine application in neurophysiology: The pros and cons in Italy. Issue 12 (December 2016) - Stipa, G.; Carletti, S.; Colosimo, C.; Frondizi, D.; Fanelli, C.; Giorgi, L.; Pasqui, R.; Gabbrielli, F.
Abstract : In many countries Telemedicine is regularly employed, i.e.: US, Canada. Although, Telemedicine use has been planned in the "Digital Agenda 2020", only few countries in Europe extensively adopt it (France, Norway, Finland, Denmark). In Italy Telemedicine services show different development levels and they are widespread in few Regions (Emilia Romagna, Veneto, Lombardia). In Terni S. Maria Hospital is underway experimental Telemedicine project coordinated by local Unit of Neurophysiology, using patented technology. Standard and monitoring EEGs are recorded through wireless system, using lan-WiFi for connection. Laptop PC with Remote Desktop software keeps control of EEG working station. EEG recorded data can be visualized on the neurophysiologist PC everywhere. Medical report of EEGs are validated through electronic signature. This method has been technically and methodologically evaluated by Italian Ministry of Public Function (Ex-DIGITPA) and considered correct. Relevant advantages has been documented: effective and faster diagnosis, safety VPN connection, freeware program of Remote Desktop, conformity with privacy rules on data recording, any adjunctive cost comparing with traditional procedure, except unavoidable initial investment for system projecting. Approval by Umbria Regional Health Authorities of Telemedicine use in clinical practice appears necessary to ameliorate safety, quality and availability of health services for patients.